Variation in parental care in the spectacled tyrant Hymenops perspicillatus is associated with increased nest predation in grassland fragments - Pretelli, Matías Guillermo (2016)
Predation risk on birds is often an important source of natural selection that shapes parental care and may promote behavioral changes. Parents can often estimate certain risks and adjust their behavior to reduce the likelihood of nest predation. The fragmentation of habitats is one of the main consequences of loss of habitats, and in general, for birds breeding in smaller patches, their daily nest-survival rate is lower due to increased nest predation. Since nest survival is an estimate of predation risk in the environment, we evaluated the daily survival rate (DSR) for nests of spectacled tyrants (Hymenops perspicillatus) and parental care behavior on fragmented and unfragmented grasslands. We conducted nest searching and monitoring during the 2012-2013 breeding season in small patches and in a continuous patch of grassland. In addition, parental activity was recorded using video monitoring. We found a lower DSR for the spectacled tyrant in fragmented grasslands, associated with increased nest predation risk; females showed a variation in parental care. This variation was evidenced by larger incubation bouts and lower visitation rate during the incubation period, and by a lower food delivery rate to nestlings, compensated by larger prey sizes. The results show that fragmentation not only reduces the fitness of individuals and impacts adversely on population, but individuals are also subjected to a strong selection pressure, and their reproductive success may depend to some extent on the ability of parents to estimate at least certain predation risk and adjust their behavior in this regard.